PLASMID-ASSOCIATED VIRULENCE OF YERSINIA PSEUDOTUBERCULOSIS AND INFECTIOUS PROCESS - L. M. Somova; F. N. Shubin; E. I. Drobot; N. G. Plekhova; I. N. Lyapun (Журнал микробиологии, эпидемиологии и иммунобиологии, 2016)
Literature data regarding genetically determined pathogenicity factors of Y. pseudotuberculosis and associated manifestations of this infection caused by various plasmid types of the causative agent are generalized. Principal attention is given to features of cell-tissue alterations mediated by virulence plasmid pYV, as well as effects of pathogenicity of an understudied pVM82 plasmid present only in Y. pseudotuberculosis strains causing clinical-epidemic manifestation of the infections as Far East scarlet-like fever (FESLF). The data obtained on the abihty of far-eastern strains to produce YPMa super-antigen, Y. pseudotuberculosis-derivative mitogen A, probably give evidence on its key role in FESLF pathogenesis. Variability of damage of innate immunity cells and target-organs caused by various plasmid types of Y. pseudotuberculosis by virulence could determine polymorphism of clinical-morphological manifestations of this infection. In-depth understanding of dependency of immune pathogenesis mechanisms of the disease on molecular characteristics of the causative agent opens up perspectives of enhancement of diagnostics and prognosis of the severity of the course of pseudotuberculosis and yersiniosis in human in general.